Thyroid nodules: ultrasonographic stratification of malignant risk by TIRADS - Thomas, George; S., Surumi; John, Anulekha Mary (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Thyroid neoplasia is easily diagnosed with, noninvasive imaging modality like ultrasonography that is widely available. TIRADS scoring is a useful modality in establishing better stratification of cancer risk in thyroid nodules, particularly, papillary thyroid cancers (PTC) as well as papillary thyroid microcancers (PTMC). Methods: All patients who presented with thyroid swelling and underwent surgery in the department of ENT were included in this study. All patients were evaluated with ultrasonographic examination of the neck. The decision of surgery was based on TIRADS scoring, size of swelling, or patient preference. Ultrasound features of the nodules, number of malignant features and TIRADS scoring were compared with final histopathology of the tumors. Results: A total of 58 thyroid surgeries were performed from January 2014 to December 2017. On statistical analysis, we found that more the number of radiological features favouring malignancy more were the likelihood of finding malignant histopathology. Conclusions: Ultrasonographic features of malignancy along with TIRADS scoring are an extremely useful tool in diagnosing thyroid cancers and will help in standardising all sonographic reports.